2016
DOI: 10.1038/srep32074
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical comparison of human and porcine skin before and after preservation by freezing for medical device development

Abstract: Collecting human skin samples for medical research, including developing microneedle-based medical devices, is challenging and time-consuming. Researchers rely on human skin substitutes and skin preservation techniques, such as freezing, to overcome the lack of skin availability. Porcine skin is considered the best substitute to human skin, but their mechanical resemblance has not been fully validated. We provide a direct mechanical comparison between human and porcine skin samples using a conventional mechano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 38 publications
4
119
0
1
Order By: Relevance
“…Further, the height difference between the microridges and depressed gaps was maintained even when the TRIM films were stretched (Figure 3c), demonstrating the flexibility of the films. Nanoindentation studies further showed that TRIM films matched the mechanical compliance of human skin (with stiffness of 0.01 N mm −1 ) 24. Our measurements done in hydrated conditions revealed that the stiffness of TRIM film at 25 °C was 0.007 ± 0.001 N mm −1 while there was an increase to 0.011 ± 0.001 N mm −1 at 40 °C (Figure S7, Supporting Information).…”
supporting
confidence: 51%
“…Further, the height difference between the microridges and depressed gaps was maintained even when the TRIM films were stretched (Figure 3c), demonstrating the flexibility of the films. Nanoindentation studies further showed that TRIM films matched the mechanical compliance of human skin (with stiffness of 0.01 N mm −1 ) 24. Our measurements done in hydrated conditions revealed that the stiffness of TRIM film at 25 °C was 0.007 ± 0.001 N mm −1 while there was an increase to 0.011 ± 0.001 N mm −1 at 40 °C (Figure S7, Supporting Information).…”
supporting
confidence: 51%
“…The gauche / trans ratio of ceramides is stable at 20°C to 40°C and radically transforms above 60°C , confirming that the differences between the lipid conformations cannot have been caused by the experimental conditions. The conformation of keratin was also unchanged below 120°C , but the keratin stiffness was higher in frozen than in defrozen porcine skin, showing structural changes . An effect of freezing on the skin barrier function has not been found .…”
Section: Discussionmentioning
confidence: 88%
“…Porcine ear skin is widely used as an ex vivo model for human skin in vivo in dermatology, because it is easily obtainable , is similar morphologically , histologically , immunohistochemically , dermatopharmacokinetically and has other similar biological properties, for example, for wound healing . A well‐studied aspect of porcine skin is its suitability as an ex vivo model for human skin barrier function investigations, that is, drug/cosmetics penetration , which is mostly identical or slightly different .…”
Section: Introductionmentioning
confidence: 99%
“…Foultz (1992) tested rat skin specimens and concluded that “freezing did not affect the resistance of the skin to tensile deformation.” Caro-Betellene et al (2015, 2016) examined different preservation methods and concluded that cryopreservation is the only way to maintain the mechanical behavior of fresh samples. More recently, Ranamukhaarachchi et al (2016) compared fresh and frozen porcine and human skin specimens, under conditions of microindentation and microneedle insertion. They found significant influence of freezing, but the tests used probed the tissue only locally and not at high stretch levels, making it difficult to extrapolate their conclusions to the uniaxial tensile deformation.…”
mentioning
confidence: 99%